اﻟﺗﺳﺎﻣﺢ واﻟﻌدل اﻻﺟﺗﻣﺎﻋﻲ ﻓﻲ اﻟﺣﺿﺎرة اﻹﺳﻼﻣﯾﺔ ﻋﻧد اﺋﻣﺔ أھل اﻟﺑﯾت ﻋﻠﯾﮭم اﻟﺳﻼم - ا. م.د.خضر عبد الرضا جاسم الخفاجي (College of Education for Women, 2019)
Subject of research is the tolerance and the social fairness in the islamic civilization for the imams of Ahl al-Bayt (peace be upon them), one of the places value and wide in the dimensions of intellectual and practical, the principle of equality and tolerance with people is an integral part of ethics required in the social and economic relations, politics and all walks of life systems the general components of the Islamic civilization. Which witnessed in the proposals and applications imams of Ahl al-Bayt (peace be upon them) this impotance and reasons were behind my choice for this subject grabbed in my research: equality and religious tolerance with the people of disclosure, and reviewed the tolerance of the faithful Ali bin Abi Talib (peace be upon him) with his murderer, and dealt with equality when Imam Hussein (peace be upon him) among his sons and freed slaves, and of tolerance and soft carpet at the Imam Ali bin Al-Hussein (peace be upon him) a large share in my research and came to the tolerance and polite people in the thinking of leading scholars of the house, and tolerance with those who Esponhm (practical applications of tolerance). The most important sources which, according to research in the forefront: The Book almahsen - of the wire (d. 274 AH / 887 CE), and the book Bihar al Anwar, Majlisi (d. 1111 AH / 1699 AD), and references Book Encyclopedia of Imam Ali bin Abi Talib (peace be upon him) in the Qur'aan and Sunnah and History - Reyshahri, book objects and Shiites - the Secretary, and other books, according to the value of research and has sustained. so we show that : The moral positions of the great Imam Hussein (peace be upon him) in the application of equality between the structure and freed slaves clarify the status of rights he has and to condemn all racist non-civilized, he explained (peace be upon him) there is no difference in the application of equality, tolerance, moral with slaves and servants, or with the gentlemen and those with status in the community, because the language of tolerance, morality human civilization in general. and the Imams of the Ahl- Bayt (peace be upon them) were calling for compassion and sympathy, and visits and familiarity and tolerance among the people to build a community of sophisticated Islamic civilization .